The Challenges of Being a Mother and an Academic Researcher during the COVID-19 Pandemic in Brazil - Collier de Mendonça, Maria; Friere de Oliveira-Cruz, Milena (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
Mothers all over the world are feeling overwhelmed and exhausted during the COVID-19 pandemic. Academic mothers, particularly, have been struggling with deadlines and productivity demands. In fact, mothers are experiencing the most challenging time in the recent history of Brazil while working and mothering children from home. In this paper, we argue Brazilian academic mothers’ challenges, which were already pervasive and inherent in Brazilian society before COVID-19, have become even more taxing due the current right-wing government’s policies in the pandemic that have exacerbated existing inequalities. Based on a literature review and quantitative and qualitative data, we present key findings of the ongoing research project—“Brazilian Mothers, Media, and COVID-19”—to illustrate the difficulties the pandemic has caused for Brazilian mothers. We note how patriarchal motherhood still shapes the ways many of Brazilian women mother their children, as they remain isolated, deal with maternal roles individually, and have little social or governmental support. Finally, we highlight the need for Brazilian mothers to learn how to mother their children with media literacy and conclude by bringing some hope to this unacceptable scenario by encouraging further collaboration among academic mothers in Brazil.